HUBUNGAN HIGIENE SANITASI TERHADAP KONTAMINASI COLIFORM PADA DEPOT AIR MINUM ISI ULANG DI KOTA DEPOK TAHUN 2022 - Nandita Ardrafitri Saraswati (2023)
Refill drinking water is still the main consumption of the community even though from its bacteriological quality it poses a risk of causing digestive diseases. The purpose of this study was to determine the relationship between place sanitation, equipment sanitation and hygiene handling with coliform contamination at refill drinking water depots in Pancoran Mas District. The type of research used is analytic observational with a cross-sectional study design. A total of 50 depots were selected as samples by using total sampling technique. A checklist sheet was used to collect data. Data were analyzed by using a Chi-Square test. The results showed that 38 of 50 depots (76%) were contaminated with coliform, 31 of 50 depots (62%) had poor sanitation, 3 of 50 depots (6%) had poor sanitation of equipment, 35 of 50 depots (70 %) the cleanliness of the handlers was poor. There is no relationship between place sanitation, sanitation, equipment and handler hygiene to coliform contamination (p-value = 0.171; p-value = 1; p-value = 0.471). It is suggested to entrepreneurs to pay attention to the condition of the production equipment including the feasibility, completeness and quality of the equipment in order to produce quality drinking water